Prevalence of unprotected anal intercourse and unprotected vaginal intercourse among HIV-positive men who have sex with men in China: a meta-analysis. Issue 3 (8th December 2011) - He, Qian; Peng, Wen-Jia; Zhang, Jun-Qing; Wang, Bing-Xiang; Wang, Jing
Abstract : This study aims at deriving a general description of the prevalence of unprotected anal intercourse among HIV-positive MSM in China using published epidemiological research. Comprehensively searching Wanfang, Weipu, China Biological Medicine (CBM), Chinese National Knowledge Infrastructure (CNKI) and Pubmed databases in the systematic review. Meta-analysis were conducted over a final set of nineteen studies (n=1603). The pooled prevalence of unprotected anal intercourse among HIV-positive MSM was 75.4% (95%CI: 67.5%∼82.5%) and unprotected vaginal intercourse was 68.0% (95%CI: 46.0%∼86.4%). The prevalence of unprotected anal intercourse differed significantly in sampling method, data collection method, sample size, location, recruitment setting and data collection period. Studies with the following features had a higher prevalence of unprotected anal intercourse: recruiting participants from 2005 to 2007, sample size being below 50, recruiting participants from MSM venues/internet, using convenience sampling, study location being Chongqing city, and using interviewer administered questionnaire. Findings from this meta-analysis indicate that a majority percentage of HIV-positive MSM engage in unprotected sexual behavior. So that place their sex partners at risk for infecting HIV and also place themselves at risk for other sexually transmitted diseases. An effective strategy for prevention and control is required for this specific population in China.